Prediksi Penjualan Obat Dengan Algoritma Regresi Linear - Dichi Setiawan; Nurhadi Surojudin; Wahyu Hadikristanto (DPPM Universitas Pelita Bangsa, 2022)
Medicine is one part of the process of health services, such as hospitals, clinics or other health services. Linear regression is used to find out how the dependent variable can be predicted through independent variables or predictor variables. Prediction of total future drug sales per month can be known through the use of drug sales datasets through a predictive method approach through structured stages in analyzing the data used. The application of a simple Linear Regression algorithm model can be implemented properly and is able to show a new insight for the prediction needs of the condition of drug sales per month in the future for the next 12 months. Performance testing of the models and algorithms used in the evaluation can produce an overview that is relevant to the scenario being modeled. The RMSE value obtained when evaluating the model's performance is 0.452 +/- 0.000 through the RapidMiner Studio application. Keywords: Data Mining, Linear Regression, Medicine